Ateliê do IPREDE: contribuições da arte e da formação estética para crianças em situação de vulnerabilidade social - Larripa, Tamara Queiroz Bezerra (2020)
This dissertation is the result of a Qualitative Research in Education carried out from a Case Study (BOGDAN & BIKLEN, 1994) on the extension project “Atelier do IPREDE: aesthetic experience in the 3rd sector”, developed by the Federal University of Ceará (UFC) in partnership with the Instituto da Primeira Infância (IPREDE) in Fortaleza - CE. Its general objective is to investigate how art and aesthetic formation can influence the development of the child, strengthen family ties and promote the rights of these children, who are mostly in a situation of extreme social vulnerability and violation of their rights. It has as subjects participating in the research, 20 mothers whose children attended at the institution, a pilot group of 10 children with their respective guardians and 10 professionals from the institution (pediatrician, social workers, psychologists, speech therapist, physiotherapists, receptionists). Uses the research procedures: Documental Analysis, Itinerancy Journal (Barbier, 2002), Focus Group and Semi-Structured Interviews in order to identify and analyze the contributions of artistic and aesthetic experiences promoted through storytelling, children's drawing , theatrical shows, videos and other artistic approaches for the children participating in the project from September 2017 to August 2018. It brings as main theoretical contributions, the approaches on aesthetic formation and education of the sensitive from Duarte Jr (2001), experience from Larrosa (2002), children's rights from Dallari and Korczak (1986), early childhood by Maturana & Verden-Zöller (2004), storytelling by Machado (2015) and children's drawing by Goldberg (2016) and Stern (1978). As a result, positive changes in children's development were identified in relation to learning, concentration, creativity, improvement in the school context, in socialization, in affection and in strengthening the family bond, revealing the importance of the work developed by “Ateliê do Iprede” and the significant contributions of art and aesthetic formation for children in socially vulnerable situations served by IPREDE.